“I cannot see your fear!” Altered recognition of fearful facial expressions in anorexia nervosa - Vaioli, Giulia; Bastoni, Ilaria; Villa, Valentina; Mendolicchio, Leonardo; Castelnuovo, Gianluca; Mauro, Alessandro; Scarpina, Federica (Frontiers in Psychology, 2023)
Background. The evidence about facial emotion recognition in Anorexia Nervosa as the role of alexithymic traits on this emotional ability is conflicting and heterogeneous.Objective. We assessed the capability in recognizing facial expressions of two primary emotions, fear and anger, in the context of Anorexia Nervosa.Methods. Women affected by Anorexia Nervosa were compared with healthy weight women in a well-established implicit facial emotion recognition task. Both reaction time and level of accuracy were computed. Moreover, the individual levels of alexithymia were assessed through a standard selfreport questionnaire.Results. Participants with Anorexia Nervosa reported a significantly lower performance in terms of reaction time and accuracy when the emotion of fearbut not angerwas the target. Notably, such an alteration was linked to the levels of alexithymia reported in the self-report questionnaire.In Anorexia Nervosa, difficulties in processing facial fearful (but not angry) expression may be observed as linked to higher expressions of alexithymic traits. We suggested future research in which emotional processing will be investigated taking into account the role of the bodily dimensions of emotional awareness.